Deskripsi Mutu Pelayanan Kesehatan di Puskesmas Guntur 1 - Dewi Sri Rahayu; Sururim Maudlunah; Rani Tiara Desty (Indonesian Journal of Health Community, 2023)
The quality of health services is all customer expectations through continuous improvement through the processes that are carried out. Guntur I Health Center still has several obstacles including the distribution of human resources is still uneven and the pattern of staffing is not appropriate so that health efforts are less effective, as well as limited infrastructure such as inadequate buildings, inadequate medical devices. The aim of this research is to provide an overview regarding the quality of health services at the Guntur Health Center 1. Quantitative research using a descriptive observational study research design, using a cross-sectional research design approach. This research was conducted at the Guntur 1 Health Center in December 2022. Sampling used a purposive sampling method. This research instrument uses a questionnaire, how to collect data by interview and Google form. The results of the research on the quality of patient safety services are not good. Quality of service effectiveness of good service. The quality of patient-centered services is good. Timely service quality is good. Service efficiency is good. Fairness in serving patients is not good. Suggestions for the Puskesmas agency are expected to add health facilities and health workers must provide more effective services.